Development of a Problem Based Learning Module for Class XI SMAK Arastamar Lotu Academic Year 2021/2022 - Rintis Kharisna Putri Zega; Ratna Natalia Mendrofa; Yulisman Zega (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The problems in this study are educators who have not used the mathematics learning module in the teaching and learning process and the low learning outcomes of students because of the lack of students' ability to construct the knowledge they acquire. The objectives of this research are: to know the feasibility of learning modules, to know practicality, to know the effectiveness of problem-based learning-based learning modules in the material for class XI SMAK Arastamar Lotu lines and sequences in the learning process. This research is a development research using the ADDIE development model which consists of analysis, design, development, implementation, and evaluation stages. The instrument used is a validation questionnaire which includes aspects of content feasibility, presentation feasibility, and design feasibility, student response questionnaires and learning achievement tests. Research result; (1) module content validity reached an average percentage of 94.84% (very feasible), language validity achieved an average percentage of 100% with very feasible criteria, design validity achieved an average percentage of 95% with very feasible criteria. (2) the practicality of the module based on the corporate test reached a percentage of 95.65% with very practical criteria, small group tests reached a percentage of 91.95% with very practical criteria, field tests reached a percentage of 91.68% with very practical criteria, (3) effectiveness the module reaches a percentage of 90% with very effective criteria.